PENGARUH REKAYASA AKRUAL UNTUK MEMINIMALKAN PAJAK - IMAN AKHADI (Media Bisnis, 2015)
This study aimed to determine which method of independent variables that have been determined, the Changes in Current Assets, Changes in Current Liabilities, Changes in Cash and Cash Equivalent, Change in Long Term Liabilities, Changes in Depreciation and Changes in Total Assets that have a greater role in efforts to minimize corporate income taxes. This research was conducted on company property and real estate sectors listed on the Indonesia Stock Exchange in the period 2004-2008. The results showed that all of the variables do not affect the total accruals.